PPh ATAU PPN: MENAKAR KEBIJAKAN PERPAJAKAN TERHADAP CRYPTOCURRENCY DI INDONESIA - Muhammad Rafi Bakri; Anastasya Utami; Alif Muhammad Hakim (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Cryptocurrency is a blockchain-based technology that is being used for any activity so that it has the potential to increase state revenue, primarily from taxation. This study aims to measure what kind of tax policy can be applied to cryptocurrencies in Indonesia. This research uses a descriptive qualitative method using secondary data. Secondary data was obtained through journals, books, and tax laws. Based on this research, cryptocurrencies can be subject to income tax and value-added tax. However, the imposition of VAT is not very potent. This is because cryptocurrencies in Indonesia are more often an investment instrument. VAT can be charged if cryptocurrency is legalized as a legal tender in Indonesia. Therefore, the current tax policy on cryptocurrencies in Indonesia is more appropriate to use the income tax.